Neurological manifestations associated with SARS-CoV-2 and other coronaviruses: A narrative review for clinicians - Maury, A.; Lyoubi, A.; Peiffer-Smadja, N.; de Broucker, T.; Meppiel, E. (Revue neurologique, 2021)
The past two decades have been marked by three epidemics linked to emerging coronaviruses. The COVID-19 pandemic highlighted the existence of neurological manifestations associated with SARS-CoV-2 infection and raised the question of the neuropathogenicity of coronaviruses. The aim of this review was to summarize the current data about neurological manifestations and diseases linked to human coronaviruses. Articles have been identified by searches of PubMed and Google scholar up to September 25, 2020, using a combination of coronavirus and neurology search terms and adding relevant references in the articles. We found five cohorts providing prevalence data of neurological symptoms among a total of 2533 hospitalized COVID-19 patients, and articles focusing on COVID-19 patients with neurological manifestations including a total of 580 patients. Neurological symptoms involved up to 73% of COVID-19 hospitalized patients, and were mostly headache, myalgias and impaired consciousness. Central nervous system (CNS) manifestations reported in COVID-19 were mostly non-specific encephalopathies that represented between 13% and 40% of all neurological manifestations; post-infectious syndromes including acute demyelinating encephalomyelitis (ADEM, n=13), acute necrotizing encephalopathy (ANE, n=4), Bickerstaff's encephalitis (n=5), generalized myoclonus (n=3) and acute transverse myelitis (n=7); other encephalitis including limbic encephalitis (n=9) and miscellaneous encephalitis with variable radiologic findings (n=26); acute cerebrovascular diseases including ischemic strokes (between 1.3% and 4.7% of COVID-19 patients), hemorrhagic strokes (n=17), cerebral venous thrombosis (n=8) and posterior reversible encephalopathy (n=5). Peripheral nervous system (PNS) manifestations reported in COVID-19 were the following: Guillain–Barré syndrome (n=31) and variants including Miller Fisher syndrome (n=3), polyneuritis cranialis (n=2) and facial diplegia (n=2); isolated oculomotor neuropathy (n=6); critical illness myopathy (n=6). Neuropathological studies in COVID-19 patients demonstrated different patterns of CNS damage, mostly ischemic and hemorrhagic changes with few cases of inflammatory injuries. Only one case suggested SARS-CoV-2 infiltration in endothelial and neural cells. We found 10 case reports or case series describing 22 patients with neurological manifestations associated with other human coronaviruses. Among them we found four MERS patients with ADEM or Bickerstaff's encephalitis, two SARS patients with encephalitis who had a positive SARS-CoV PCR in cerebrospinal fluid, five patients with ischemic strokes associated with SARS, eight MERS patients with critical illness neuromyopathy and one MERS patient with Guillain–Barré Syndrome. An autopsy study on SARS-CoV patients demonstrated the presence of the virus in the brain of eight patients. The wide range of neurological manifestations and diseases associated with SARS-CoV-2 is consistent with multiple pathogenic pathways including post-infectious mechanisms, septic-associated encephalopathies, coagulopathy or endothelitis. There was no definite evidence to support direct neuropathogenicity of SARS-CoV-2.